Palmar cutaneous nerve conduction in patients with carpal tunnel syndrome. (2nd November 2015) - Uluc, Kayihan; Aktas, Ilknur; Sunter, Gulin; Kahraman Koytak, Pinar; Akyuz, Gulseren; İsak, Baris; Tanridag, Tulin; Us, Onder
Abstract : Objective: This study aimed to assess palmar cutaneous branch of the median nerve (PCBm) conduction in patients with clinically diagnosed carpal tunnel syndrome (CTS), to compare PCBm conduction with that of the median and ulnar nerves, and to determine the PCBm conduction abnormality rate in patients with CTS. Materials and Methods: The study included 99 hands of 60 patients with clinical CTS and 38 hands of 38 healthy controls. Sensory nerve conduction study (NCS) was performed on the median nerve, ulnar nerve, and PCBm, and onset latency, conduction velocity and amplitude were recorded. Additionally, differences in latency and velocity between the median nerve and PCBm, and the difference in latency between the median and ulnar nerves were calculated. Results: In all, 56% of the patients with CTS had abnormal PCBm conduction. Additionally, in 7 of 8 hands with abnormal sensation –both in the thenar eminence and abnormal sensory distribution along the main branch –NCS of the PCBm was also abnormal. Conclusions: The PCBm is not ideal as a comparator nerve for the neurophysiological diagnosis of CTS. The frequency of PCBm abnormality in CTS patients may be related to the concomitant damage in both of these nerves. Additionally, the present findings may help explain, at least in part, why patients with CTS often exhibit sensory involvement beyond the classical median nerve sensory borders.